2021
DOI: 10.5488/cmp.24.13001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of paramagnetic and ferromagnetic phases of an Ising model on a third-order Cayley tree

Abstract: In this present paper, the recurrence equations of an Ising model with three coupling constants on a third-order Cayley tree are obtained. Paramagnetic and ferromagnetic phases associated with the Ising model are characterized. Types of phases and partition functions corresponding to the model are rigorously studied. Exact solutions of the mentioned model are compared with the numerical results given in Ganikhodjaev et al. [J. Concr. Appl. Math., 2011, 9, No. 1, 26-34].

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…The most interesting finding here is that the phase transition occurs when both J and J p are negative (in the anti-ferromagnetic case). For the Ising model with the same Hamiltonian, no phase transition has occurred in the anti-ferromagnetic regimes in previous studies (see [16,22]).…”
Section: Discussionmentioning
confidence: 65%
“…The most interesting finding here is that the phase transition occurs when both J and J p are negative (in the anti-ferromagnetic case). For the Ising model with the same Hamiltonian, no phase transition has occurred in the anti-ferromagnetic regimes in previous studies (see [16,22]).…”
Section: Discussionmentioning
confidence: 65%
“…Mech., 2022, 053204], using the Kolmogorov consistency theorem, we established the translation invariant splitting Gibbs measures (TISGMs) connected to the Ising model with mixed spin (1,1/2) on the second-order Cayley tree. We showed that the mixed spin Ising model comprises three TISGMs in both the ferromagnetic and antiferromagnetic regions, in contrast to the classic Ising model [ [101], Akın, H., Physica B, 2022, 645, 414221]. In this context, considering the theoretical results, detailed analysis of the transitions between phases will be carried out by drawing phase diagrams.…”
Section: Acknowledgementsmentioning
confidence: 98%
“…• On a Cayley tree of order three, Akın [101] has recently analytically analysed the recurrence equations of an Ising model with three competing interactions. He precisely described the Ising model's paramagnetic and ferromagnetic phases.…”
Section: -37mentioning
confidence: 99%
“…In Ref. [16], we proved that the (1,1/2)-MSIM on a CT of order two has three TIGMs in both the ferromagnetic and anti-ferromagnetic regions, while the Ising model having single-spin [18,19,20,21,22] does not have such GMs in the anti-ferromagnetic region. At the same time, for the Potts models [23] on the CT, the phase transition occurs only in the ferromagnetic regime.…”
Section: Introductionmentioning
confidence: 95%
“…When performing in both ferromagnetic and anti-ferromagnetic regimes, since |λ 3 (θ, k)| > 1, there are repelling fixed points. The repelling fixed points indicate that there exists more than one GM and phase transition happens, while the singlespin Ising model does not have the TIGMs in the anti-ferromagnetic regime [18,20,21,33,37,38].…”
mentioning
confidence: 97%